Polyphony in the Epilogue of Anna Akhmatova's Requiem - Ерохина, Ирина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article focuses on the functioning of crossing quotations in Anna Akhmatova's Requiem. The author demonstrates that the image of the monument in the Epilogue is based on complex semantic relationships with the genre model of XXX Ode by Horace and the reminiscences of Dante's Divine Comedy.